ANALISIS SIFAT FISIK ASAP CAIR KAYU AKASIA DAUN KECIL (Acacia auriculiformis) BERDASARKAN MASA SIMPAN - Miftahul Jannah; Henny Arryati; Trisnu Satriadi (Universitas Lambung Mangkurat, 2020)
Indonesia is one of the countries with a tropical climate and has a vast forest area with a distribution that is found throughout the Indonesian region and has so many benefits. One of the abundant wood in Indonesia is acacia wood. The pulp and paper industry makes acacia wood as the main raw material to be made pulp (pulp) and then processed into finished materials in the form of paper. Besides being used as a raw material for processing acacia pulp and paper, it is also used as a raw material for processing liquid smoke. This study aims to determine the quality of the physical properties of liquid smoke of small leaf acacia wood (Acacia auriculiformis) based on shelf life. This research was conducted at the Banjarbaru Industrial Standardization and Research Center, for 5 months. The test parameters of the physical properties of liquid smoke such as water content, odor, color, transparency (gross content) and pH are compared to the quality standards of liquid smoke from Japan. Test parameters that almost meet Japanese standards at a shelf life of 3 months compared to a shelf life of 1 and 2 months, the odor produced is typical of liquid smoke, the resulting pH is 3.29, transparency 0.03, the resulting color is brown and the moisture content produced.Keywords: Liquid smoke; Small Leaf Acacia; Shelf life, Water content; Transparency; pH; Smell; Color